Aspek Fukugoudoushi Kiru Nuku dan Toosu dalam Kalimat Bahasa Jepang Sehari-hari Oleh Orang Jepang di Bali - Dipraja, Gede Boy Sistha Nanda; Rauh Artana, I Nyoman; Budiana, I Made (Humanis; Vol 24 No 1 (2020)DO - 10.24843/JH.2020.v24.i01.p04, 2020)
The tittle of this research is ”the aspects of compound verb kiru, nuku, and toosu that used in daily japanese by Japanese people in Bali” that aimed to research the form, type, grammatical meaning and substitution of compound verb kiru, nuku, and toosu in daily Japanese that used by Japanese people in Bali. This research was analysed using descriptive method, formal and informal technique. Form and the type of compound verb kiru, nuku, and toosu reference analysis used syntax theory by Chaer (2012). Compound verb comprehension refers to Takanao (1984). Grammatical meaning was analysed using grammatical verb theory by Pateda (2001) and grammatical meaning concept of compound verb kiru, nuku, toosu by Kurita (2015), Himeno (1980), Yoshiyuki (1977) dan Kindaichi (1976). Result of this reasearch is compound verbs kiru, nuku and toosu can form continous, repetitive and prefective aspects when combined with another verbs that showing aspect and used in renyoukei form. These verb should be keizoku doushi, shunkan doushi and joutai doushi. Based on analysis result, compound words kiru, nuku, and toosu in Japanese grammatically means event ended intentionally, event occured unexpectedly, event as the lastest limit, and activity is carried out continuously until finished. B ased on the analysis result known that compound verb kiru, nuku, and toosu have the same grammatical meaning and should be substituted. Viewed from japanese grammatical perspectives, the compound verbkiru, nuku, and toosu  explained the event carried out continuously until the end and explained that the activity done repeatedly until finished.